The Images of Science Through Cultural Lenses A Chinese Study on the Nature of Science - Ma, Hongming; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Are the images of science held by learners the same across cultures? What are the implications for science education? This book explores the nature of science from a cultural perspective. Located in the Chinese cultural context, the book examines the nexus between characteristics of Chinese thinking and the understanding of the nature of science in Chinese traditional culture. The dramatic cultural change as a result of the introduction of Western culture was accompanied by the dramatic reconstruction of the image of science. The Chinese science education echoes the understanding of the nature of science in each cultural historical period. Reflecting the tension and dilemmas of understanding the nature of science at the policy making level, the images of science held by Chinese science teachers represent a mixture of influences by values and beliefs that are embedded in the imported science and by Chinese native cultural beliefs. The book concludes with suggestions of change of practice in science education for a more realistic image of science not only within the field of education but also in society at large.
Keywords: Education; Education; Education (general).